XVII. International Conference on Logistics in Agriculture 2023: Conference Proceedings (University of Maribor Press, 2023)
17th International Conference on Agricultural Logistics organized by: Landscape Governance College GRM Novo mesto, Grm Novo mesto – center of Biotechnology and Tourism, the Faculty of Logistics of the University of Maribor, the Municipality of Sevnica and Cooperatice Union of Slovenia. The central theme of this year’s conference will be “Climate changes of logistics in agriculture“. The conference has become traditional and paves the way for a different view of logistics in connection with agriculture.